Influence of viscous dissipation on the boundary layer flow of Cu-Al2O3 hybrid nanofluid - Bing, Kho Yap; Rahimah, Jusoh; Mohd Zuki, Salleh; Zulkhibri, Ismail; Mohd Hisyam, Ariff (Pushpa Publishing House, 2021)
This study presents the mathematical modelling of two dimensional boundary layer flow of hybrid nanofluid where the impact of viscous dissipation has been accentuated in the energy equation. The copper and aluminium oxide nanoparticles are considered in this study. The surface of the model is stretched and shrunk at certain values of stretching/shrinking parameter. The partial differential equations of the hybrid nanofluid are reduced to the ordinary differential equations with the utilization of the suitable similarity transformations. Then Matlab software is utilized to produce the numerical and graphical results by implementing the bvp4c function. Subsequently, dual solutions are obtained with the correct guess values. The insertion of viscous dissipation in this model tremendously lessens the rate of heat transfer. Besides, the effects of the suction and nanoparticles concentration also have been highlighted. An increment in the suction parameter and concentration of copper enhance the magnitude of the reduced skin friction coefficient while the augmentation of the aluminium oxide nanoparticles shows a different trend.